2010
DOI: 10.1002/ijc.24923
|View full text |Cite
|
Sign up to set email alerts
|

Unifying roles for regulatory T cells and inflammation in cancer

Abstract: Activities of CD4+ regulatory (TREG) cells restore immune homeostasis during chronic inflammatory disorders. Roles for TREG cells in inflammation-associated cancers, however, are paradoxical. It is widely believed that TREG function in cancer mainly to suppress protective anticancer responses. However, we demonstrate here that TREG cells also function to reduce cancer risk throughout the body by efficiently downregulating inflammation arising from the gastrointestinal (GI) tract. Building on a “hygiene hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
137
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(155 citation statements)
references
References 71 publications
(165 reference statements)
17
137
0
Order By: Relevance
“…An additional benefit is that sterile extracts of microbes have fewer health risks for immune-compromised patients, lowering risk of microbial overgrowth in patients who may otherwise suffer inappropriate immune responses. Some earlier work has suggested that killed bacteria or their extracts have healthful antiinflammatory properties, in particular during inflammatory bowel conditions [82][83][84][85][86]. Precise characterization of the dog bacterial extract and potential in human subjects remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit is that sterile extracts of microbes have fewer health risks for immune-compromised patients, lowering risk of microbial overgrowth in patients who may otherwise suffer inappropriate immune responses. Some earlier work has suggested that killed bacteria or their extracts have healthful antiinflammatory properties, in particular during inflammatory bowel conditions [82][83][84][85][86]. Precise characterization of the dog bacterial extract and potential in human subjects remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although Tregs may reduce the risk of inflammation-associated cancer by downregulating inflammation, it is believed that, in cancer, they mainly function by suppressing the antitumor immune response. However, under poorly regulated pro-inflammatory conditions, Tregs fail to inhibit, and may stimulate, a proinflammatory T helper 17 (Th17) response, driving the pro-carcinogenic process (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL-23, a heterodimer produced by dendritic cells (DC) comprising the unique p19 subunit plus the p40 subunit in common with IL-12, also contributes to differentiation and maintenance of Th17 cells (8). Moreover, recent data indicate late-stage plasticity of a subpopulation of Tregs, which can be selectively induced to adopt a Th17 phenotype, suggesting that Tregs may do more to modulate cancer than simply block constructive anticancer responses (5).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies in mice we have shown that some GI tract bacteria induce regulatory T-cells (Treg) of increased anti-inflammatory potency, which in turn counteract epithelial tumors throughout the body, instead of promoting them through anti-tumor immunity downregulation (6,(8)(9)(10)(11). Importantly, the bacteria-primed Treg activate clinically silent local GI tract and systematic immunity networks, which confer decreased risk of epithelial carcinogenesis (10,11).…”
Section: Introductionmentioning
confidence: 99%